The research objectives are to evaluate physical and mechanical properties of OSB based on strand orientations made from akasia wood (Acacia mangium Wild) and afrika wood (Maesopsis eminii Engl). Akasia and afrika wood are used for OSB strand material with phenol formaldehyde (PF) as adhesives and addition of paraffin. OSB made in this research consists of three plies whereas are differed into eight strand orientations. Hot press was carried out at 160ºC and pressure 25 kg/cm² for 15 minutes. D - NURHAIDA .; Naresworo NUGROHO; Dede HERMAWAN (Jurnal Ilmu dan Teknologi Hasil Hutan, 2008)
The research objectives are to evaluate physical and mechanical properties of OSB based on strand orientations made from akasia wood (Acacia mangium Wild) and afrika wood (Maesopsis eminii Engl). Akasia and afrika wood are used for OSB strand material with phenol formaldehyde (PF) as adhesives and addition of paraffin. OSB made in this research consists of three plies whereas are differed into eight strand orientations.  Hot press was carried out at 160ºC and pressure 25 kg/cm² for 15 minutes. Determination of OSB physical and mechanical properties referred to JIS A 5908-2003. Result showed that strand orientations have not affected to OSB physical properties except for linear swelling 24 h, but it significantly influences all mechanical properties of OSB. Wood species has an effect on mechanical properties of OSB in the dry test, wet MOE lengthwise test and OSB physical properties, particularly to OSB density and water absorbing capability at 2 h and 24 h.  All of OSB physical properties are meet JIS A 5908-2003 standard, but not all of the mechanical properties such as dry MOE lengthwise, dry MOE and MOR widthwise. The best physical and mechanical properties is presented by OSB made from akasia wood in strand orientation F (core layer is orientated and surface layers are in random, R°/0°/R°), G (core layer is orientated 45° and surface layers are in random, R°/45°/R°), B (surface strand direction is upright to core strand direction, 0°/90º/0°), and C (core layer is in random, surface layers are orientated, 0°/R/0°) whereas all parameters meet JIS A 5908-2003 standard. In comparation with strand orientation B that is frequent used in industry, strand orientation F and G are proficient to raise the modulus elasticity value (MOE) and strength (MOR) as much as 167.8-231.7% and 89.7-109.9%, respectively; especially in widthwise board application. Furthermore, strand orientation F and G are more flexible as structural components. Keywords:   Oriented strand board, strand orientation, phenol formaldehyde